Kit-dependent discrepancy in D16S539 and general considerations for database matches - Zajac, Barbara Karolina; Zehner, Richard; Scheiper, Stefanie; Weissenberger, Melanie (Forensic science international. Genetics, 2018)
Throughout the last decade more companies have been offering multiplex PCR kits for forensic STR typing. As a consequence, it has been demonstrated, that an observed genotype may unexpectedly vary at a single locus when different STR kits have been used. Analysing STR profiles which have to be entered in a national database, unknown or undetected primer binding site mutations, insertions or deletions within the flanking region of STR loci may hinder matches and therefore have far-reaching consequences. The current study is a further example indicating that sequence variations in flanking regions are a common problem within STR typing which should not be underestimated. A deletion of 16 nucleotides close to the primer binding site downstream of the repeat sequence resulted in deviant genotypes at the D16S539 locus according to different STR kits used.